Ouch! - Orme, David; Blake, Beccy (Wayland London, 2008)
"Dad hit his thumb with a hammer. Jess was stung a bee. Then Sam banged his head. Ouch! Freddy told them all to be brave. But sometimes being brave isn't easy."--Publisher's description